The impact of land transfer on food security: the mediating role of environmental regulation and green technology innovation - Xu, Ming; Lu, Zhaoyang; Wang, Xinyue; Hou, Guangwei (Frontiers in Environmental Science, 2025)
IntroductionFood security is the lifeblood of national security and an important cornerstone for world 15 peace, stability, and development. In this context, the study of the impact of land transfer (TF) on food security (FS) provides a new perspective for land resource optimization.MethodsBased on the empirical data of 30 provinces and regions in China from 2010 to 2022, this paper used the two-way fixed effect model to explore the causal relationship and the intermediary relationship between the two. Moreover, quantile regression is used to further explore the heterogeneity. In addition, the spatial Durbin model is used to analyze the spillover effect.ResultsFirst, land transfer has a significant promoting effect on food security. Secondly, land transfer has obvious heterogeneity to food security. Third, environmental regulation and green technology innovation play an intermediary role in land transfer to food security. Fourth, land transfer has a spatial spillover effect on food security.DiscussionThis paper not only enriches the theoretical research on the impact of land transfer on food security, but also provides empirical evidence. It provides an important reference for deepening China’s land transfer policy system, optimizing land transfer resources and ensuring the safety of grain industry.